The strangest thing in the sea : and other curious creatures of the deep - Poliquin, Rachel, 1975- (Kids Can Press, 2021)
"In this weird guessing game, the most peculiar and little-known marine animals vie for the title of strangest thing in the sea. Each bizarre beast, disguised as a preposterous thing, will give clues about its true identity. Open the flap to reveal the real creature and all of its quirky adaptations, along with lots of facts!"--Back cover.